Thrombolytic Treatment in Wake‐Up Stroke: A Propensity Score–Matched Analysis of Treatment Effectiveness in the Norwegian Stroke Registry - Mary‐Helen Søyland; Arnstein Tveiten; Agnethe Eltoft; Halvor Øygarden; Torunn Varmdal; Bent Indredavik; Ellisiv B. Mathiesen (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
Background Previous clinical trials found improved outcome of thrombolytic treatment in patients with ischemic wake‐up stroke (WUS) selected by advanced imaging techniques. The authors assessed the effectiveness of thrombolytic treatment in patients with WUS in a nationwide stroke registry. Methods and Results Using propensity score matching, the authors assessed the effectiveness and safety of thrombolytic treatment versus no thrombolytic treatment in 726 patients (363 matched pairs) with WUS in the Norwegian Stroke Registry in 2014 to 2019. Thrombolytic treatment in WUS versus known‐onset stroke was compared in 730 patients (365 matched pairs). Functional outcomes were assessed by the modified Rankin Scale (mRS) at 3 months. A significant benefit of thrombolytic treatment in WUS was seen in ordinal analysis (odds ratio [OR], 1.48 [95% CI, 1.15–1.91]; P=0.003) and for mRS 0 to 2 (OR, 1.81 [95% CI, 1.29–2.52]; P=0.001) but not for mRS 0 or 1 (OR, 1.32 [95% CI, 1.00–1.74]; P=0.050). The proportion of patients with mRS 0 or 1 was lower in patients with WUS who underwent thrombolysis versus those with known‐onset stroke (50.4% versus 59.5%; OR, 0.69 [95% CI, 0.52–0.93]; P=0.013), while outcomes were similar between groups for mRS 0 to 2 and ordinal analysis. Symptomatic intracranial hemorrhage after thrombolytic treatment occurred in 4.4% of patients with WUS and 3.9% of patients with known‐onset stroke (OR, 1.14 [95% CI, 0.54–2.41]; P=0.726). Conclusions Thrombolytic treatment in patients with WUS was associated with improved functional outcome compared with patients with no thrombolytic treatment and was not associated with increased rates of symptomatic intracranial hemorrhage compared with known‐onset stroke. The results indicate that thrombolytic treatment is effective and safe in WUS in a real‐life setting.